Sclerophyllous vegetation dynamics in the north of the Iberian peninsula during the last 16,000 years - RAMIL-REGO, P; RODRÍGUEZ-GUITIÁN, M; MUÑOZ-SOBRINO, C (Global Ecology and Biogeography, 1998)
We used pollen analysis to evaluate the dynamics of sclerophyllous arboreal taxa during the last 16,000 years. Quercus ilex type pollen and, to a lesser degree, other sclerophyllous elements (e.g. Olea and Phillyrea) have been documented during the Late-glacial in the majority of the sequences obtained in continental territories in the north of the Iberian peninsula, as well as in the eastern coastal/sub-coastal area in the Cantabric region. During the Late-glacial and the Holocene, sclerophyllous elements became widespread in many areas of the north Iberian peninsula (the Sil, Duero and Ebro depressions and the southernmost slopes of adjacent mountains), with the smallest pollinic representation of these taxa being for the most septentrional areas (coastal/sub-coastal territories and the northermost slopes of the Cantabrian-Atlantic Mountains). During these periods, there is no indication of the presence of Quercus ilex pollen in the northwestern territories, which would explain the absence of this species in the present-day landscape. Despite the widespread distribution that sclerophyllous elements have maintained during the last 16,000 years, they have never attained a predominant role in the landscape, having a smaller representation, both during hotter and colder phases, than deciduous forests, pine forests and mixed forests.
Keywords: Holocene; iberian peninsula; Late-glacial; palynology; Quercus ilex; sclerophyllous forests; species range; vegetation history